2019
DOI: 10.1089/sur.2018.135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacteriophage Anti-Biofilm Activity for Potential Control of Orthopedic Implant-Related Infections Caused byStaphylococcus aureus

Abstract: Combined, these data demonstrate the in vitro efficacy of S. aureus-specific bacteriophage cocktails against S. aureus growing on porous titanium and warrant further in vivo studies in a clinically relevant animal model to evaluate the potential application of bacteriophage in the management of PJI caused by S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 31 publications
0
57
0
Order By: Relevance
“…Disease control requires bacterial biofilm disruption, as demonstrated at least in the case of human pathogens (Fong et al, 2017;Morris et al, 2019). Using CLSM analysis, we found that after 6h of incubation, Xccϕ1 disrupts the stability of Xcc biofilm (Figure 4).…”
Section: Discussionmentioning
confidence: 87%
“…Disease control requires bacterial biofilm disruption, as demonstrated at least in the case of human pathogens (Fong et al, 2017;Morris et al, 2019). Using CLSM analysis, we found that after 6h of incubation, Xccϕ1 disrupts the stability of Xcc biofilm (Figure 4).…”
Section: Discussionmentioning
confidence: 87%
“…Some reports have shown the efficiency of phages therapy in medical, veterinary, agricultural, and aquaculture applications without adverse safety concerns for eukaryotic cells. 13,37,38 Phages administration has shown to stimulate the host immune response, depending on the route of administration, e.g., oral and topical administrations may induce the production of anti-phages neutralizing antibodies, while intravenous administration of phages has the potential to stimulate innate and adaptive immune responses. 13,39 No significant differences were identified on the local tissue response following the implantation of phages-loaded hydrogels, sustaining their biosafety profile.…”
Section: Discussionmentioning
confidence: 99%
“…13,37,38 Phages administration has shown to stimulate the host immune response, depending on the route of administration, e.g., oral and topical administrations may induce the production of anti-phages neutralizing antibodies, while intravenous administration of phages has the potential to stimulate innate and adaptive immune responses. 13,39 No significant differences were identified on the local tissue response following the implantation of phages-loaded hydrogels, sustaining their biosafety profile. Moreover, by in vitro cytocompatibility, it was observed that phages and hydrogels' leachable products did not interfere with osteoblastic cells' viability, proliferation and morphology, indicating that the phage-loaded biomaterial systems could allow for bone cells spreading and growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations